2021
DOI: 10.1200/jco.20.01171
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Safety of Osimertinib: A Review of Data

Abstract: PURPOSE Osimertinib is a third-generation, CNS-active, irreversible, oral epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI) that potently and selectively inhibits both EGFR-TKI-sensitizing and T790M resistance mutations. We assess the cardiac failure risk in patients receiving osimertinib by evaluating the available data. METHODS Post hoc analyses of cardiac data from (1) studies in patients with advanced non–small-cell lung cancer, FLAURA (osimertinib, n = 279; comparator EGFR-TKI, n = 277… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
42
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 36 publications
0
42
0
1
Order By: Relevance
“… 25 Certain TKIs (e.g., lapatinib, imatinib, osimertinib) inhibit hERG potassium channels and cause a delay in cardiac repolarization, thus leading to QTc prolongation. 3 , 5 , 26 In our study, QTc prolongation AEs as assessed by local ECG reading occurred in 3% of patients and were all of low grade (≤1). Maximum increase in QTcF value from baseline of more than 30 msec to less than or equal to 60 msec was observed in 17 patients (9.4%), all from the 40 mg to 240 mg cohort.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“… 25 Certain TKIs (e.g., lapatinib, imatinib, osimertinib) inhibit hERG potassium channels and cause a delay in cardiac repolarization, thus leading to QTc prolongation. 3 , 5 , 26 In our study, QTc prolongation AEs as assessed by local ECG reading occurred in 3% of patients and were all of low grade (≤1). Maximum increase in QTcF value from baseline of more than 30 msec to less than or equal to 60 msec was observed in 17 patients (9.4%), all from the 40 mg to 240 mg cohort.…”
Section: Discussionmentioning
confidence: 49%
“… 29 In randomized controlled trials, rates of cardiotoxicity were higher in the osimertinib than in the control treatment arms, and a pooled analysis of the AURA3 and FLAURA trials found that 3.9% of osimertinib-treated patients had both a minimum postbaseline LVEF value of less than 50% and a maximum decrease in LVEF value of greater than or equal to 10 percentage points from baseline. 26 Taken together, these findings suggest that it is advisable to monitor for signs of cardiotoxicity in patients receiving EGFR TKIs, particularly osimertinib.…”
Section: Discussionmentioning
confidence: 95%
“…However, because of LVEF decreases that were observed in patients with cardiac risk factors before osimertinib treatment, cardiac monitoring, including an assessment of LVEF at baseline and during osimertinib treatment, is advised." 3 The allegation by Anand et al 1 that "[t]he authors truly misrepresent the data" is unfortunate, and the readers of the Journal of Clinical Oncology may be assured that our analyses are appropriate, and the data presented are factual and correct. Notwithstanding this, we appreciate the opportunity to address questions regarding what was reported, and what could not be seen because of the nature and prognosis of the disease being treated.…”
mentioning
confidence: 98%
“…2 Both letters raise concerns regarding our reporting of the cardiac safety of osimertinib. Anand et al 1 state that our paper 3 "…would lead a reader to believe that osimertinib has no cardiotoxicity…" and Kunimasa 2 asks "…is osimertinib-induced LVEF [left ventricular ejection fraction] reduction really a harmless toxicity?" What we stated with clarity is that our "…data do not suggest a causal relationship between osimertinib and cardiac failure.…”
mentioning
confidence: 99%
“… 3 With regard to osimertinib, the reported level of ejection fraction decrease in pooled data was 3.9%. 4 The reported events were mostly asymptomatic and resolved without treatment of the event or osimertinib discontinuation.…”
mentioning
confidence: 99%